2017
DOI: 10.1016/j.juro.2017.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Patterns of Care and Outcomes of Men Found to Have Lymph Node Metastases at the Time of Radical Prostatectomy

Abstract: Purpose A thorough understanding of the natural history and consensus regarding the optimal management of pathologic lymph node-positive (pN1) prostate cancer are lacking. Our objective was to describe patterns of care and outcomes of a contemporary cohort of men with pN1 prostate cancer. Materials and Methods The National Cancer Data Base (NCDB) was used to identify 7,791 men who were found to have LN metastases at the time of radical prostatectomy (RP). Multinomial logistic regression and Cox proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Moreover, although a RCT specifically designed in the pN1 setting demonstrated that immediate androgen deprivation therapy (aADT) might be associated with a survival benefit, its results might not be generalizable to contemporary pN1 patients due to the inclusion of patients diagnosed in the pre-PSA era with high nodal burden [4,5]. Finally, despite the fact that all patients with LNI are categorized as pN1 regardless of the number and location of positive nodes according to the TNM classification, the long-term prognosis of this group is highly heterogeneous and varies significantly according to disease characteristics [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although a RCT specifically designed in the pN1 setting demonstrated that immediate androgen deprivation therapy (aADT) might be associated with a survival benefit, its results might not be generalizable to contemporary pN1 patients due to the inclusion of patients diagnosed in the pre-PSA era with high nodal burden [4,5]. Finally, despite the fact that all patients with LNI are categorized as pN1 regardless of the number and location of positive nodes according to the TNM classification, the long-term prognosis of this group is highly heterogeneous and varies significantly according to disease characteristics [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they have recently reported a higher CSS with adjuvant RT than with salvage RT [ 30 ]. Consistently, expectant management for pN1 was associated with inferior survival than adjuvant treatment including RT in retrospective case series and database studies [ 24 , 27 , 28 , 31 ]. In contrast, the RADICALS-RT trial that enrolled mainly pN0 or pNx in addition to pN1 patients has recently reported a comparable BCR rate between adjuvant RT and salvage RT [ 32 ].…”
Section: The Prognosis In Pn1 Prostate Cancer By Treatmentsmentioning
confidence: 90%
“…Supplementary Material 1, http://links.lww.com/ COU/A36 presents a multivariate analysis of the effect of different management strategies on overall and/or cancer-specific survival. aADT was not found to have any benefit in overall survival [10,11,14,15] nor in cancer-specific mortality [11]) compared to observation. Similarly, aRT alone had no survival advantage over observation [14,15].…”
Section: Management Outcomes Patients Featuresmentioning
confidence: 90%